Implementasi Multilayer Perceptron untuk Klasifikasi Berita Hoax dalam Media Sosial - Amanda, Hervilla; Faiza, Nayla; Sofinah Harahap, Lailan (UNIVERSITAS SERAMBI MEKKAH, 2025)
The very fast dissemination of information via social media in the current digital era has facilitated the spread of fake news or hoaxes. Hoax news is false information, often created deliberately to spread or manipulate public opinion. The spread of hoaxes on social media can have serious impacts, such as public unrest. Therefore, automatic detection of hoax news is very important to maintain the integrity of information circulating in society. This research aims to implement the Multilayer Perceptron (MLP) algorithm in classifying news as